Cover Picture: Structural Insights into the Trp‐Cage Folding Intermediate Formation (Chem. Eur. J. 8/2013). Issue 8 (11th February 2013) - Rovó, Petra; Stráner, Pál; Láng, András; Bartha, István; Huszár, Kristóf; Nyitray, László; Perczel, András
<x xml:space="preserve">Abstract</x> The folding energy landscape of the smallest protein, the 20‐residue long Trp‐cage, is more rugged than expected. Temperature‐dependent NMR measurements revealed that at neutral pH the final step of the Trp‐cage folding is a fast secondary structural rearrangement: the short α‐helical G11–G15 segment of the intermediate (I) converts into a 310‐helix and thus, the polypeptide adopts the most stable, folded (F) structure. At acidic pH the isomerization of the G11P12 peptide bond slows down the folding process: two off‐pathway intermediate unfolded states (U′ and U′′) emerge. These two states have no native‐like structure and show elevated internal mobility. For more information see the Full Paper by A. Perczel et al. on page 2628 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>